Synthesis of chitosan-stabilised bimetallic nanoparticles containing Fe and Ni and the reductive degradation of nimesulide - Gonçalves, Andressa Aparecida; Araújo, Annelise França; Pires, Manoel José Mendes; Verly, Rodrigo Moreira; Franco, Débora Vilela; da Silva, Leonardo Morais (Eclética Química, 2018)
Chitosan (CHI)-stabilised Ni–Fe bimetallic nanoparticles (bNP/CHI) were synthesised varying the content of nickel and denoted as 2-bNP/CHI, 17-bNP/CHI, and 27-bNP/CHI. The nanoparticles were characterised using several techniques and used in the removal of nimesulide. XRD and Mössbauer analyses confirmed the formation of an amorphous structure containing Fe0 and Fe2O3 while the FT-IR analysis confirmed the presence of chitosan in the nanoparticles. A very high removal of nimesulide was obtained after only 15 min of treatment with the 17-bNP/CHI system. The by-product obtained after the reductive treatment was identified using the chromatography analysis coupled to the mass spectrometry technique.